2006
DOI: 10.1086/506470
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Really Know about Cosmic Acceleration?

Abstract: Essentially all of our knowledge of the acceleration history of the Universe -including the acceleration itself -is predicated upon the validity of general relativity. Without recourse to this assumption, we use SNeIa to analyze the expansion history and find (i) very strong (5σ) evidence for a period of acceleration, (ii) strong evidence that the acceleration has not been constant, (iii) evidence for an earlier period of deceleration and (iv) only weak evidence that the Universe has not been decelerating sinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
183
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(194 citation statements)
references
References 37 publications
11
183
0
Order By: Relevance
“…We could ignore the reconstruction in the region of high redshift (Huterer & Starkman 2003;Shapiro & Turner 2006) or add a physically motivated model for H base in Eq. (10), which would provide us with the value we expect to measure in the upper redshift bound (Tang et al 2008).…”
Section: Minimizing the Bias In The Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could ignore the reconstruction in the region of high redshift (Huterer & Starkman 2003;Shapiro & Turner 2006) or add a physically motivated model for H base in Eq. (10), which would provide us with the value we expect to measure in the upper redshift bound (Tang et al 2008).…”
Section: Minimizing the Bias In The Reconstructionmentioning
confidence: 99%
“…The importance of a model-independent reconstruction of the cosmic expansion rate has already been investigated in the literature (Huterer & Turner 1999, 2000Tegmark 2002;Wang & Tegmark 2005;Mignone & Bartelmann 2008). In this context, PCA has been used to reconstruct the dark-energy equation of state (Huterer & Starkman 2003;Crittenden et al 2009;Simpson & Bridle 2006) and the deceleration parameter (Shapiro & Turner 2006) as a function of redshift. The use of PCA was also proposed in the interpretation of future experiments results by Albrecht et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the reconstruction of q(z), it was found that the strongest evidence of acceleration happens at redshift z ∼ 0.2 [8,9,10], and the evidence of the current acceleration is not very strong [9] and model dependent [10]. Previous studies on the reconstruction of w(z) also showed that the stringent constraint on w(z), or the sweet spot, happened around redshift z ∼ 0.2 − 0.5 [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 96%
“…There are very strong model-independent evidences [10] (see also e.g. [11]) for the accelerated expansion.…”
Section: Introductionmentioning
confidence: 98%